The Effect of Service Quality and Corporate Image on Customer Loyalty: The Mediating Role of Customer Satisfaction - Elisabet Tambunan; Mery Lani Purba; Marupa Siregar; Roberto Roy Purba; Hanna Khan; Anastasia Manalu (CV. Sakura Digital Nusantara, 2026)
Purpose: This study examines the effects of service quality and corporate image on customer loyalty, with customer satisfaction as a mediating variable, in the banking sector in North Sumatra, Indonesia. The study is grounded in SERVQUAL theory, Expectation-Confirmation Theory (ECT), and Relationship Marketing Theory to explain the mechanisms of loyalty formation. Design/methodology/approach: A quantitative explanatory design was employed using a cross-sectional survey of 210 active bank customers selected through purposive sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test both direct and indirect relationships among the constructs. Findings: The results indicate that service quality has a significant positive effect on customer loyalty (β = 0.393) and customer satisfaction (β = 0.795). Corporate image significantly influences customer satisfaction (β = 0.343) but does not directly affect customer loyalty (β = −0.043). Customer satisfaction significantly affects customer loyalty (β = 0.182). Mediation analysis shows that customer satisfaction does not mediate the relationship between service quality and customer loyalty, but significantly mediates the relationship between corporate image and customer loyalty. Research implications/limitations: This study contributes to theory by demonstrating that customer satisfaction acts as a selective mediator, distinguishing between functional and perceptual antecedents of loyalty. However, the cross-sectional design, regional sample, and reliance on self-reported data limit generalizability and causal inference.